Rewealth! : Stake Your Claim in the $2 Trillion Redevelopment Trend that's Renewing the World - Cunningham, Storm, 1951- (New York McGraw-Hill, 2008)
"In ReWealth! redevelopment expert Storm Cunningham reveals a vast new realm of fast-growing, highly profitable opportunities to revitalize our communities and our planet. He outlines new practices and strategies that achieve rapid, resilient renewal, generating tremendous wealth - not to mention personal satisfaction and happiness - through remarkable career and investment options." "Cunningham explains the three proven, universal principles that, when combined, enable nondestructive, unlimited economic growth that actually heals nature and society. He shows how you can generate rewealth by replenishing natural resources, rebuilding communities, redeveloping polluted land, restoring structures, and revitalizing economies."
Include Index
Keywords: Real estate development -- Restoration ecology -- Sustainable development